Role of Dual-Energy Computed Tomography in Gallbladder Disease: A Review - Tarvinder Singh; Pankaj Gupta (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Gallbladder diseases are common and include a spectrum ranging from benign to cancer. Imaging plays an integral role in the diagnosis and in guiding appropriate management. While most patients with gallstone (GS) diseases can be evaluated with ultrasound, those with complicated GS disease, suspicion of cancer, or staging of cancer need additional cross-sectional imaging. Computed tomography (CT) is widely available and is often the imaging test of choice following an equivocal ultrasound or negative ultrasound in patients with unexplained symptoms. Conventional CT has limited sensitivity in detecting GS or common bile duct stones. In other scenarios, including diagnosis of acute cholecystitis (AC) and characterization of gallbladder wall thickening, an increase in accuracy using novel techniques is desirable. Dual-energy computed tomography (DECT) is increasingly incorporated into clinical practice. DECT has shown promising results in the detection of cholesterol stones that otherwise go unnoticed on conventional CT. However, its role beyond GS disease has largely been unexplored. In this review, we discuss the available literature on the DECT in biliary diseases and discuss the potential applications of this technique.